COMPETITIVENESS OF ENTERPRISES OF THE ROAD INDUSTRY IN THE PERIOD OF REFORMS AND ECONOMIC INSTABILITY - KUPALOVA, Halina (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The length and quality characteristics of public highways in Ukraine compared to the leading countries of the world were analyzed. Positive trends in the road construction and repair market related to the reform of the road industry were identified: decentralization of roads, financing of road repairs through the implemented State Road Fund of Ukraine, formation of a competitive environment, increase in the number of players in the road construction and repair market, strengthening of state control in the field procurement and road construction. Attention is drawn to the negative factors that affect the market situation, the formation of competitive advantages of enterprises, taking into account the specifics of the road industry. A set of measures to strengthen the competitiveness of enterprises is proposed, taking into account the results of the implemented reforms. It is considered expedient to intensify the development of public-private partnership, in particular, through the concession mechanism. To improve the quality management of road works, road monitoring should be improved using the HDM-4 automated road development and management system. The current legal framework in terms of the implementation of international forms of contracts, including FIDIC, NEC, needs to be updated. A promising direction for improving the management of enterprises in the road industry of Ukraine is the implementation of information modeling in construction, namely the use of digital technologies for building information models of VIM - technologies. The key task is to ensure a clear, transparent system of procurement and setting prices for construction, repair works and services. The implementation of the specified measures will contribute to increasing the level of validity of operational and strategic management decisions to ensure the effective functioning and development of enterprises in the road industry of Ukraine.
Keywords: competitiveness; enterprise; road industry; reform; monitoring; management; roads; highways; road length; road quality; road infrastructure; road construction and repair market; public-private partnership; information modeling; procurement